Evaluation of IgG binding capability to SARS-CoV-2 variants in early COVID-19 convalescent sera using an indirect ELISA - Behzad Hussain; Peizhe Zhao; Yu Liu; Bo Yang; Xiaoxiong Li; Zhichao Zhang; Guoqiang Feng; Demei Zhang; Defen Lu; Wu Changxin (Virus Research)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a single-stranded RNA virus which has resulted in the Coronavirus Disease 2019 (COVID-19) pandemic and has infected millions of people all over the world. SARS-CoV-2 has been mutating rapidly resulting in the emergence of multiple variants to escape the host immune system mainly by mutations in its receptor binding domain (RBD) of the spike protein. The RBD and full-length spike of SARS-CoV-2 are the main targets of the neutralizing antibodies (mainly IgGs). Many SARS-CoV-2 variants are considered to have potential to escape from the host immune system. This rapid evolution of the virus posed a great challenge regarding the efficacy and effectiveness of the current SARS-CoV-2 vaccines. Hence, in this study, RBD of Alpha, Beta, Gamma, Kappa and Omicron BA.1 and full-length spike of BA.1, BA.2, BA.3, BA.4/5, BQ.1.1 and XBB.1.5 Omicron variants were used as coating antigens in an indirect Enzyme Linked Immuno-Sorbent Assay (ELISA) to check the IgG binding capability to the COVID-19 convalescent sera from patients of first wave of infection occurring in Wuhan. Our results show that the currently circulating Omicron BQ.1.1, XBB.1.5 and previous Omicron BA.1, BA.2 and BA.4/5 do not show significant reduction in binding, while Omicron BA.3 and previous variants Alpha, Beta, Gamma, Kappa, and Omicron showed a significantly reduced binding when compared to the wild-type Wuhan strain. These results indicate that the patients recovering from natural infection of early original Wuhan strain may have the potential to resist infection of current circulating variants and the vaccines using the prototype antigen may still work for newly emerged variants.